Cooperativism as a strategy to insertion of the land reform settlers in dynamic markets: the case of COPERTERRA - Ferreira, Gabriel Murad Velloso; Ende, Marta Von; Rossés, Gustavo Fontinelli; Neumann, Pedro Selvino (Revista de Administração da UFSM, 2019)
This study aims to analyze, through a cooperative, the role of social organization in the insertion of the land reform settlers of the city of Tupanciretã - RS in the dynamic markets of the milk production chain. For this, a study was conducted in the Regional Agrarian Reform Cooperative Mother Earth - COPERTERRA. As main results, it was found that the Coperterra is inserted in dynamic markets and has shown that dairy activity fits the reality of the small farms, since that provides a monthly income and that the risks to the seasonality of production can be mitigated with planning and organization of animal feed. Moreover, this activity enables farmers have time to dedicate to the production of other food, which ensures diversification of property. It is worth noting that 10% of the milk produced is industrialized and traded in the institutional markets.